Konseling Keluarga Persfektif Q.S At-Tahrim Ayat 6 (Tafsir Al-Misbah, Ibnu Katsir, Kementerian Agama RI) - Sabrial, Jumli; Irman (Conseils : Jurnal Bimbingan dan Konseling Islam, 2024)
This article aims to discuss family counseling from the perspective of the Al-Qur'an Surah At-Tahrim Verse 6, using the literature study research method. The findings of this research focus on the interpretation of Surah At-Tahrim verse 6, studied from the perspective of the Tafsir Al Misbah, Tafsir Ibnu Katsir and Tafsir of the Ministry of Religion of the Republic of Indonesia, namely: family counseling, when viewed from the perspective of Surah At-Tahrim verse 6, has a significant role. crucial in forming a harmonious family, rooted in religious values, and preparing family members to follow God's commands. Through family counseling, family members can deepen their understanding of their duties and responsibilities in implementing religious teachings, while strengthening emotional and social ties between them.